2021
DOI: 10.3390/nu13113839
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota as a Contributor to Chronic Inflammation and Its Potential Modifications

Abstract: The gut microbiota is a crucial factor in maintaining homeostasis. The presence of commensal microorganisms leads to the stimulation of the immune system and its maturation. In turn, dysbiosis with an impaired intestinal barrier leads to accelerated contact of microbiota with the host’s immune cells. Microbial structural parts, i.e., pathogen-associated molecular patterns (PAMPs), such as flagellin (FLG), peptidoglycan (PGN), lipoteichoic acid (LTA), and lipopolysaccharide (LPS), induce inflammation via activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 127 publications
0
46
0
3
Order By: Relevance
“…Local inflammation is triggered, and the intestinal wall permeability increases. LPS can then pass through the intestinal wall, enter the bloodstream, and cause systemic inflammation in other target tissues [ 21 ].…”
Section: Gut Microbiota In Health and Diseasementioning
confidence: 99%
“…Local inflammation is triggered, and the intestinal wall permeability increases. LPS can then pass through the intestinal wall, enter the bloodstream, and cause systemic inflammation in other target tissues [ 21 ].…”
Section: Gut Microbiota In Health and Diseasementioning
confidence: 99%
“…Colorectal cancer (CRC) is the 2nd leading cause of cancer-related deaths in United States 1 and develops as a result of complex interactions between microbiota, dietary components, and gut mucosal immune/inflammatory mediators. [2][3][4] Multiple research efforts have associated the differential impact of human gut microbiota and microbiota-associated metabolism changes with CRC. 2,3,[5][6][7][8][9] Given the high CRC incidence and mortality statistics, host and environmental factors that affect CRC, alongside novel agents that modulate host and gut microbial metabolism merit attention to reduce CRC.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that intestinal inflammation and, in particular, pro-inflammatory cytokine secretion are correlated with changes in the composition of gut microbiota [ 59 , 64 ]. We made a correlation study between the different bacterial taxa quantified in the cecum and plasma cytokine levels ( Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%